2016
DOI: 10.1016/j.neuroimage.2015.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic processing is distributed across the language system

Abstract: Language comprehension recruits an extended set of regions in the human brain. Is syntactic processing localized to a particular region or regions within this system, or is it distributed across the entire ensemble of brain regions that support high-level linguistic processing? Evidence from aphasic patients is more consistent with the latter possibility: damage to many different language regions and to white-matter tracts connecting them has been shown to lead to similar syntactic comprehension deficits. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
147
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(184 citation statements)
references
References 180 publications
(249 reference statements)
19
147
2
Order By: Relevance
“…The recent data [46] provide evidence that sensitivity to syntactic complexity is widespread across the language system, contrary to many previous neuroimaging studies that reported only a few, localized foci of syntactic complexity effects.…”
Section: Neurophysiological Mechanisms Underlying Language Developmentcontrasting
confidence: 99%
“…The recent data [46] provide evidence that sensitivity to syntactic complexity is widespread across the language system, contrary to many previous neuroimaging studies that reported only a few, localized foci of syntactic complexity effects.…”
Section: Neurophysiological Mechanisms Underlying Language Developmentcontrasting
confidence: 99%
“…However, it accords with fMRI work that observes sensitivity to lexical and syntactic processing throughout the language network (e.g., refs. 28,51,53,61,62), and evidence that language regions form a highly integrated functional system (e.g., ref. 63).…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent fMRI work has been able to extricate overlapping sets of neural activity in the auditory cortex to identify distinct responses to either speech or music (Norman-Haignere et al, 2015). Furthermore, correlations between resting-state fMRI and gene expression have also recently been uncovered (Hawrylycz et al, 2015; Richiardi et al, 2015; Wang et al, 2015), but future studies that combine such approaches with speech-related task-based imaging, including investigations beyond traditional areas of speech and language (Blank et al, 2015) should provide insights into genomic correlates of speech and a deeper understanding of speech-related brain networks.…”
Section: Future Directionsmentioning
confidence: 99%